Answer:
Option B) The simplification performed in step 2 is invalid or incorrect
The value of w in the given expression is -54
Explanation:
Option B) The simplification performed in step 2 is invalid or incorrect
The corrected steps are given below :
GIven expression is
and x=2y
To find w when y=-2 :
Step 1: I first substitute y=-2 into x=2y yielding x=2(-2)
Step2: I simplify the expression resulting in x=-4
Step3: I substitute x=-4 and y=-2 into the given expression
we get
![w+(-4)(-2)+3(-4)^2=2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/41lxywi7eyyici926ux4pkiybqynqp9bn3.png)
Step 4: I use order of operations to simplify and get
![w+8+3(16)=2](https://img.qammunity.org/2021/formulas/mathematics/middle-school/pn97sqs957pbn0vtrnngzzzceztmtdlpzf.png)
![w=2-56](https://img.qammunity.org/2021/formulas/mathematics/middle-school/1jc3kv1v5gk09myuh6eozcayd3s43tovdb.png)
Therefore w=-54
The value of w in the given expression is -54